PENGARUH PROFESIONALISME, LINGKUNGAN KERJA, KECERDASAN EMOSIONAL, GAYA KEPEMIMPINAN DAN BUDAYA ORGANISASI TERHADAP KINERJA PENGELOLA KEUANGAN (STUDI KASUS PADA SKPD KOTA PEKANBARU) - Muhammad Arrijalul Akbar; Desmiyawati -; Meilda Wiguna (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
The purpose of this research is to to test and prove empirically the effect of professionalism, work environment, emotional intelligence, leadership style and organizational culture to financial management performance in SKPD Pekanbaru. This research is conducted on 29 working units in Pekanbaru by using questionnaires. The sample in this study amounted to 58 respondents, while the population are involved parties in financial management in the work unit Pekanbaru. Multiple linier regression analysis was applied to analyze the data. The statistical results indicate that professionalism, Emotional Intelligence and organizational culture affects the performance of financial management, whereas the work environment and leadership style does not affect the performance of financial management. Donations influence of independent variables on the dependent variable amounted 77.5%.Keywords: performance, professionalism, environment, intelligence, leadership and culture.